A self-referencing non-destructive test method to detect damage in reinforced concrete bridge decks using nonlinear vibration response characteristics. (7th February 2022) - Hafiz, Ali; Schumacher, Thomas; Raad, Anis
Highlights: Self-referencing non-destructive test method to detect damage in reinforced concrete presented. Proposed method builds on impulse response testing using series of increasing impacts. Nonlinear vibration index proposed to detect concrete degradation and delaminations. Results confirmed with visual inspection, concrete cores, and depth of removed concrete. Overall trend found between proposed index and depth of removed concrete. Abstract: Several non-destructive test (NDT) methods, namely visual inspection, hammer sounding, chain drag, impulse response testing, impact echo testing, ultrasonic (array) echo testing, and under certain conditions ground penetrating radar (GPR) are currently used to detect and estimate the extent of damage such as delaminations in reinforced concrete bridge decks. In this article, we present a self-referencing NDT method that builds on impulse response (IR) testing to detect damage using nonlinear vibration characteristics. The hypothesis is that for an undamaged deck, varying the impact force applied to a specific test point does not affect the corresponding frequency response function (FRF) for frequencies that lie within the measurement system's linear operating range. On the other hand, the FRF for a test point that contains damage changes when the impact force is increased, indicating a nonlinear vibration response. To demonstrate that the concept works theoretically, two 2D finite element (FE) models of a bridge deck, one containing a shallow delamination, were developed and their responses to impact forces of increasing amplitude compared. IR data from an in-service bridge deck was processed and analyzed. Visual inspection results and ultra-high-pressure hydro-blasting performed on the deck for rehabilitation purposes provided an opportunity to compare the obtained results with common inspection methods and actual damage extent. Based on the observations, a new damage index, referred to as nonlinear vibration index (NVI), is proposed and shown to be sensitive to damage, including shallow delaminations that were missed by means of visual inspection.